Improving Students’ Skills in Translation through Students-Teams Achievement Division (STAD) Technique - Syarwan Ahmad (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
This classroom action rresearch was aimed at improving students’ skills in translating at the English Department of the State Islamic University (UIN) Ar-Rarniry Banda Aceh by using the Student-Teams Achievement Division (STAD) Technique. Throughout the entire cycles, students worked in groups of 4-5 persons to plan and write their translations. The study showed that the average score of pre- test (66) increased dramatically to reach 86, and moved up a little higher (87) after the second cycle. It is recommended that STAD Cooperative Technique be implemented in teaching translation courses. Key words: Teaching translation; STAD; UIN Aceh.Copyright © 2015 by Al-Ta'lim All right reserved